GROUNDWATER FLOW MODELLING OF THE ALLUVIAL AQUIFER IN THE MOURIA AREA, SW GREECE - Karapanos, E.; Burgess, W.; Lambrakis, N. (Bulletin of the Geological Society of Greece, 2010)
The objective of this paper is to study the impact of a reflooding of the former Mouria Lake on the hydraulic state of the Pyrgos area. The hydrogeological data acquired through field work were combined with the volumetric budget and the hydrological data from the entire Alfios River catchment in order to build the conceptual and numerical model of the groundwater flow system, which confirmed the hydraulic state before the drainage of the Mouria Lake. The model was also used to predict the future hydraulic state in case stresses change. For this purpose, Flowpath II, a numerical groundwater flow model, was used to evaluate the impacts of groundwater exploitation in the alluvium unconfined aquifer that is developing in the Holocene deposits. Due to the connection of the aquifer with the surface drainage canals near the coastal zone, the conceptual model was built upon irrigation data, rainfall data, and pumping rate data from the pumping stations that drain the area of the former Mouria Lake. These data were inserted in the model which was calibrated using a 24- month set of piezometric measurements. The simulation results show that the groundwater level before the drainage of the lake was 2m higher than the present situation and the same scenario will happen in case of reflooding the drained lake. Today, the pumping stations keep the groundwater level near the sea level throughout the hydrological year.